2009
DOI: 10.1130/g30433a.1
|View full text |Cite
|
Sign up to set email alerts
|

Self-shielding of thermal radiation by Chicxulub impact ejecta: Firestorm or fizzle?

Abstract: As hypervelocity ejecta from the Chicxulub (Yucatán, Mexico) impact fell back to Earth, the surface may have received a deadly dose of thermal radiation suffi cient to ignite global wildfi res. Using a two-phase fl uid fl ow code, which includes ejecta and air opacities in a radiative transfer calculation, we modeled the atmospheric reentry of spherules arriving at distal sites. The models predict a pulse of thermal radiation at the surface peaking at 5-15 kW/m 2 , analogous to an oven set on "broil" (~260° C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 23 publications
2
70
0
Order By: Relevance
“…Detailed multiphase flow models suggest that the atmospheric reentry of the ejecta spherules may have caused a global pulse of increased thermal radiation at the ground (42). Such a thermal pulse is below the lower limits of woody biomass ignition, in agreement with studies yielding no evidence for widespread large wildfires at the K-Pg boundary (43), with a possible exception for the Gulf of Mexico region close to the impact site [(9) and references therein].…”
Section: Wwwsciencemagorg Sciencesupporting
confidence: 75%
“…Detailed multiphase flow models suggest that the atmospheric reentry of the ejecta spherules may have caused a global pulse of increased thermal radiation at the ground (42). Such a thermal pulse is below the lower limits of woody biomass ignition, in agreement with studies yielding no evidence for widespread large wildfires at the K-Pg boundary (43), with a possible exception for the Gulf of Mexico region close to the impact site [(9) and references therein].…”
Section: Wwwsciencemagorg Sciencesupporting
confidence: 75%
“…The modification involved the removal of the collar and the replacement of the whip aerial with a coiled aerial. The resulting transmitter-logger packages had a total mass of around 13.0 g (mean 13.0 g, range 11.7 -13.5 g). The iButtons were programmed to record body temperature at 30 or 36 min intervals with an accuracy of 0.58C.…”
Section: (C) Proceduresmentioning
confidence: 99%
“…Much of Earth's megafauna was lost at the end of the Cretaceous, yet animals suggested as being able to shelter or hibernate appear to show preferential survival (Robertson et al 2004). One of the extreme environmental effects that follows a large impact with the Earth is the emission of thermal radiation from the hot expanding plume of vapour and debris produced immediately following the impact (Toon et al 1997;Shuvalov & Artemieva 2002) and hot impact ejecta, as they re-enter the atmosphere and decelerate (Melosh et al 1990;Goldin & Melosh 2009). An impact-induced thermal pulse at the Cretaceous-Palaeogene (K-Pg) boundary has been suggested to have resulted in the ignition of extensive wildfires (Melosh et al 1990) and thereby explains soot found at multiple K-Pg boundary localities around the globe (Wolbach et al 1985).…”
mentioning
confidence: 99%